Comparative Sentiment Analysis on Contemporary Islamic Educational Issues using Generative AI Platforms - Ahmad Muhibbin; Rizwatul Hasanah; Dwi Purwati (At-Tadris: Journal of Islamic Education, 2025)
This study aims to analyze the application of artificial intelligence (AI) in sentiment analysis of contemporary Islamic discourse, focusing on themes such as feminism, Islamic education, and Islamic politics. The research methods used include a qualitative approach, experiments with AI, and sentiment analysis using Natural Language Processing (NLP). The results of the study show that AI-based sentiment analysis such as ChatGPT, Meta AI, and Gemini AI have significant capabilities to understand contemporary Islamic discourse issues with dominant positive sentiment classifications, especially in the themes of Islamic education and gender equality. This study also highlights the importance of data accuracy and the development of AI algorithms that are more sensitive to social and religious contexts to produce more inclusive and relevant analysis.